2014
DOI: 10.1162/jocn_a_00681
|View full text |Cite
|
Sign up to set email alerts
|

Context Predicts Word Order Processing in Broca's Region

Abstract: The function of the left inferior frontal gyrus (L-IFG) is highly disputed. A number of language processing studies have linked the region to the processing of syntactical structure. Still, there is little agreement when it comes to defining why linguistic structures differ in their effects on the L-IFG. In a number of languages, the processing of object-initial sentences affects the L-IFG more than the processing of subject-initial ones, but frequency and distribution differences may act as confounding variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Interestingly, this sensitivity did not translate into a misalignment sensation, confirming that this range of AV asynchrony is perceptually well tolerated 4 . These findings are consistent with previous studies 23,24,62 showing that the IFG is involved in implicit timing 22 , a sensitivity that allows listeners to predict word order from syntactic information 63 . Even though our brain is not aware of precise event temporality, the latter is essential to monitor e.g., articulatory and syntactic correctness, and to prepare for correct production.…”
Section: The Inferior Frontal Gyrus Tracks Av Temporal Asynchronysupporting
confidence: 93%
“…Interestingly, this sensitivity did not translate into a misalignment sensation, confirming that this range of AV asynchrony is perceptually well tolerated 4 . These findings are consistent with previous studies 23,24,62 showing that the IFG is involved in implicit timing 22 , a sensitivity that allows listeners to predict word order from syntactic information 63 . Even though our brain is not aware of precise event temporality, the latter is essential to monitor e.g., articulatory and syntactic correctness, and to prepare for correct production.…”
Section: The Inferior Frontal Gyrus Tracks Av Temporal Asynchronysupporting
confidence: 93%
“…One suggestion has been that activation in Broca's region reflects general linguistic processing costs (Kristensen & Wallentin, 2015), i.e., that whenever a linguistic process for some reason is difficult or challenged, it causes Broca's region to become more active. In support of this hypothesis are well-known findings that syntactic manipulations yield increased Broca's region activation (Ben-Shachar, Palti, & Grodzinsky, 2004;Christensen & Wallentin, 2011;Kristensen, Engberg-Pedersen, Nielsen, & Wallentin, 2013;Tettamanti et al, 2009) and findings showing that Broca's region responds to unpredicted word order, rather than syntactic manipulations per se, as defined by working memory demands (Fiebach, Schlesewsky, Lohmann, VonCramon, & Friederici, 2005;Wallentin, Roepstorff, Glover, & Burgess, 2006), cloze probability (Obleser & Kotz, 2010) or context (Kristensen, Engberg-Pedersen, & Wallentin, 2014). Broca's region activation is also routinely observed in the absence of word order manipulations (Fedorenko, Duncan, & Kanwisher, 2013;Novick et al, 2010).…”
Section: Broca's Regionmentioning
confidence: 78%
“…At first glance this finding is difficult to reconcile with the literature. Previous experiments have indicated that Broca's region is indeed sensitive to certain types of frequency effects in linguistic experiments, such as word frequency (Fiebach et al, 2002;Kronbichler et al, 2004), sentence cloze probability (Obleser & Kotz, 2010) and contextual constraints on sentence structure (Kristensen et al, 2014). But these prediction violations all hinge on long-term exposure to linguistic material.…”
Section: Broca's Region (Lifg)mentioning
confidence: 97%
“…An example that shows the problem with this assumption and that specifically targets the influence of prior context on neural activation is an fMRI study of syntax by Kristensen, Engberg-Pedersen, and Wallentin (2014) . In that study, participants were presented with subject-initial sentences ( He noticed her ) and object-initial sentences ( Her, he noticed ).…”
Section: Taking Context Seriouslymentioning
confidence: 99%